Interleukin-22 Polymorphisms in Plasmodium falciparum-Infected Malaria Patients - Nada H. Aljarba; Mashael R. Al-Anazi; Mohammed I. Shafeai; Fuad H. Rudiny; Saad M. Bin Dajem; Hani Alothaid; Majid Darraj; Saad Alkahtani; Jahad Alghamdi; Mohammed N. Al-Ahdal; Ahmed A. Al-Qahtani (Hindawi Limited, 2020)
Background and Objectives. Malaria infection, caused by Plasmodium falciparum, is the most lethal and frequently culminates in severe clinical complications. Interleukin-22 (IL-22) has been implicated in several diseases including malaria. The objective of this study was to investigate the role of IL-22 gene polymorphisms in P. falciparum infection. Material and Methods. Ten single-nucleotide polymorphisms (SNPs), rs976748, rs1179246, rs2046068, rs1182844, rs2227508, rs2227513, rs2227478, rs2227481, rs2227491, and rs2227483, of IL-22 gene were genotyped through PCR-based assays of 250 P. falciparum-infected patients and 200 healthy controls. In addition, a luciferase reporter assay was done to assess the role of the rs2227513 SNP in IL-22 gene promoter activity. Results. We found that the rs2227481 TT genotype (odds ratio 0.254, confidence interval = 0.097-0.663, P=0.002) and the T allele is associated with protection against P. falciparum malaria as well as the rs2227483 AT genotype (odds ratio 0.375, confidence interval = 0.187-0.754, P=0.004). The haplotype A-T-T of rs1179246, rs1182844, and rs976748 was statistically more frequent in the control group (frequency 41%, P=0.034) as well as the haplotype A-G of rs2046068 and rs2227491 (frequency 49.4%, P=0.041). The variant rs2227513 G allele had a statistically higher activity (P<0.0001) with the luciferase reporter assay. Conclusion. The study suggests that IL-22 polymorphisms in rs2227481 and rs2227483 could contribute to protection against P. falciparum malaria. Also, the G allele of rs2227513, located in the promoter region of IL-22 gene, could be essential for higher expression levels of IL-22 cytokine.